The implementation of TQM with service quality from students perspective in Malaysian public university - Saberi, Nasarina; Romle, Abd Rahim (AENSI Publisher, 2015)
Study on service quality is related to the customer satisfaction that involved with service provider and service receiver.Customer is the main focus in service delivery because their need to be fulfill in order to maintain the quality of services on the eyes of beholder.To achieve that, previous investigation shows that there have influenced by several dimensions from total quality management (TQM) such as continuous improvement, customer focus, top management, information and communication and employee involvement. Hence, this study aims to investigate the relationship of the implementation of TQM towards on service quality.This article presents to propose a study of TQM on service quality in the Malaysian Higher Education Institutions context.